Surgical Management of Infective Endocarditis Complicated by Embolic Stroke: Practical Recommendations for Clinicians. Issue 17 (25th October 2016) - Yanagawa, Bobby; Pettersson, Gosta B.; Habib, Gilbert; Ruel, Marc; Saposnik, Gustavo; Latter, David A.; Verma, Subodh
Abstract : There has been an overall improvement in surgical mortality for patients with infective endocarditis (IE), presumably because of improved diagnosis and management, centered around a more aggressive early surgical approach. Surgery is currently performed in approximately half of all cases of IE. Improved survival in surgery-treated patients is correlated with a reduction in heart failure and the prevention of embolic sequelae. It is reported that between 20% and 40% of patients with IE present with stroke or other neurological conditions. It is for these IE patients that the timing of surgical intervention remains a point of considerable discussion and debate. Despite evidence of improved survival in IE patients with earlier surgical treatment, a significant proportion of patients with IE and preexisting neurological complications either undergo delayed surgery or do not have surgery at all, even when surgery is indicated and guideline endorsed. Physicians and surgeons are caught in a common conundrum where the urgency of the heart operation must be balanced against the real or perceived risks of neurological exacerbation. Recent data suggest that the risk of neurological exacerbation may be lower than previously believed. Current guidelines reflect a shift toward early surgery for such patients, but there continue to be important areas of clinical equipoise. Individualized clinical assessment is of major importance for decision making, and, as such, we emphasize the need for the functioning of an endocarditis team, including cardiac surgeons, cardiologists, infectious diseases specialists, neurologists, neurosurgeons, and interventional neuroradiologists. Here, we present 2 illustrative cases, critically review contemporary data, and offer conceptual and practical suggestions for clinicians to address this important, common, and often fatal cardiac condition.